Study of Iodium Content in Seaweed Juice as an Alternative for GAKI's Prevention - Endang Rohmawati; Hidayat Syarief; Sri Anna Marliyati (Media Gizi dan Keluarga, 2000)
This research was conducted to study the iodium level in seaweed (Euchema cottonii) juice as the alternative to pprevent the iodium deficiency disorders. The result showed that fresh seaweed contained 91,19 % water, 5,07 % ash, 0,27 % fat, 0,27 % protein, 3,22 % carbohydrate and 2,81 ppm iodium. However, the most preferred seaweed juice contained 83,41 % water, 0,04 % ash, 0,48 % fat, 0,15 % protein, 15,93 % carbohydrate and 1,03 ppm iodium. The characteristics of seaweed juice were as follows : iodium level ranged from 0,62 - 1,99 ppm, pH 3,14 - 3,42, acid total 0,32 - 0,51 %, glucose level 11,00 - 18,13 % and dissolved suspension total 1,35 - 1,36 Brix. The organoleptic test showed that the most preferred seaweed juice was one in comparison with water 1:7 and 25 % glucose (A3B3) supplemented